Wilhelm Slavata und sein Hauptmann Hynek Ladislav Vejtmiler von Vejtmile - Hrdlička, Josef (Theatrum historiae, 2012)
This paper analyses the quality of the relation between the aristocrat and his officer in the first half of the 17th century. It considers the content of the officer’s service and the extent to which the content was defined by the standards set by the authorities or rather the landlord’s requests caused by current needs and situation in the dominion for the administration of which the office bore responsibility. It explores the officer’s expectations on his arrival at the office as well as the possibilities, certainties and uncertainties the office involved. It also inquires what the master expected from the officer, what his requirements were, what he was willing to tolerate and what behaviour went beyond the limit of the master’s tolerance.